Pengaruh Model Quantum Teaching Terhadap Kemampuan Pemahaman Konsep Matematis Siswa SMP pada Materi Statistika - Rahmatia Rahmatia; Azis Azis (Jurnal Akademik Pendidikan Matematika, 2026)
This study aims to investigate the effect of Quantum Teaching model on the mathematical conceptual understanding ability of junior high school students in statistics. The low mathematical conceptual understanding, especially in statistics which covers data presentation, measures of central tendency, and measures of dispersion, was identified as the main problem in one of the junior high schools in Baubau City. The Quantum Teaching model through the TANDUR framework is considered capable of creating a conducive, meaningful, and motivating learning environment. This study employed a quasi-experimental design with a nonequivalent control group design. The sample consisted of two classes, each comprising 32 students: the experimental class received Quantum Teaching, while the control class received conventional instruction. The data collection instrument was a 10-item essay test measuring mathematical conceptual understanding, administered as both pretest and posttest. Learning progress was analyzed using the normalized gain score (N-gain) and an independent t-test at a 5% significance level. Results showed that the mean N-gain of the experimental class (0.63; medium category) was significantly higher than that of the control class (0.35; low-medium category), with t = -6.321 and p = 0.000 < 0.05. It is concluded that the Quantum Teaching model has a significant positive effect on the mathematical conceptual understanding of junior high school students in statistics in Baubau City.